THE ECONOMIC ERRORS OF DR. MARTIN LUTHER KING Jr. - Block, Walter E. Block; Iglesias, David R. (University of Darussalam Gontor Press, 2023)
Martin Luther King Jr. was — and still is — one of the most powerful symbols in U.S. history. His message of anti-racism along with the exposing of government corruption are just part of the impact he made on the American people. While these are the more noble and respectable of his works, there exist other areas in which Dr. King erred in his judgement. The topic to which this paper will be devoted to will be the erroneous beliefs that Dr. King advocated regarding the failures of capitalism and the push for a more democratic socialist type of economic system. It is important that readers of this work not subject themselves to the fallacy of argumentum ad verecundium — the mistake of assuming that because Dr. King was an expert in one area (civil rights), he is therefore an expert in another (economics).